(3JRhjL CejQ GdeDefjf Ydjg GdSdGe HfJg ef YeQ Hf GdNWGHs - (3GdMSjfj GdbQTj, CHh GdbGSe, GdTQja GdeQJVi, Ydj Hf GdMSjf Hf ehSi Hf eMeO Hf EHQGgje, (B436 (3g`s ((3MSf Hf YHO GdgGOj Hf ehSi GdehShj GdNQSGfjs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3SCdfj GdQFjS COGe Gddg Jecjfg Yf GdSHH aj EfcGM CejQ GdeDefjf Ydjg GdSdGe HfJg YeQ Hf GdNWGH acja jUM Pdc eY GYJbGO GdEeGejI (B...s
(3BNQgG (B:s
(3eeG jbJVjg GdYbO hGdefY ef GdYbO Chdi ef EjbGYg hGdefY ef ebJVGg hEfeG GMhL Edi Pdc GdYLR Yf PcQ GdYPQ GdUMjM hgPg LedI eZfjI Yf PcQ ShGgGs
(3JHUQI GdYfhGf (B:s
(3aj eYQV GdcdGe Yf ELGRI dgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\278s
(3GdPQjYI (B5 - 130 ( 811)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds